Animal-assisted resilience in space exploration: a human factors approach to astronaut behavioral health - David W. Kim (Frontiers in Psychology, 2026)
Space science has been developed through past and current missions of the International Space Station (ISS) and Artemis (I and II) in low Earth orbit and on the lunar surface. Numerous missions have used animals on test flights to better understand the physiological dangers of space flight for humans. A contemporary focus of space exploration is long-duration crewed travel to establish a Moon station and reach Mars. The astrotechnology of the human-less spaceflights (USA, Russia, ESA, UAE, China, and India) launched in 1965 (Mariner 4), has advanced enough to support the progressive colonization of the Red Planet with investigating equipment (Perseverance rover, Ingenuity helicopter, Hope orbiter, Tianwen-1 orbiter, and Chinese lander-rover). Are humans, then, ready to explore for deep space mission? What are major hazards that still need to be solved? Can animals play a novel role for humans in space? While the five factors of altered gravity, radiation, confinement (isolation), distance from Earth, and unknown hostile environments have been earnestly analyzed in the STEM field of space medicine, this paper initially examines the biological ripple effects of animal astronauts to mitigate risks for human astronauts as a psychological intervention model. The countermeasures of the well-being and space community security are determined considering the potential role of animals in reducing the emergence rate of behavioral health and performance decrements (loneliness, mental and emotional strain, fear, lethargy, lack of enthusiasm, and violence). This paper argues a rational hypothesis that if the engineering aspects of animal (dog) support does not reduce the scientific capabilities, the innovative policy of a ‘human-pet companionship’ can improve the cognitive, social, and physical resilience of the long-term astronauts in terms of neuroscience, safety, teamwork (communication), and mission success.